2023
DOI: 10.12775/jehs.2023.37.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects in the management of breast cancer – recent studies

Marcela Maksymowicz,
Piotr Machowiec,
Anna Korzeniowska
et al.

Abstract: Introduction and purpose Breast cancer (BC) management includes local therapies surgery, radiotherapy and systemic – hormonotherapy, chemotherapy, targeted and immunotherapy. However, some adverse events of these treatment strategies limit their wide administration in BC therapy. The aim of the study was to present adverse effects in the management of BC, prevention and treatment of them. State of the knowledge Surgery of the breast leads to lymphedema, pain, and anatomical changes. The most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…Still, chemotherapeutic drugs have problems such as poor stability, lack of tissue specificity, and short half-life, which not only lead to severe toxic side effects but also make chemotherapeutic drugs have a low concentration in tumor tissues, which can't achieve the therapeutic purpose [10,11] . In addition to this, it has also been shown that chemotherapy can lead to complications, such as anthracycline-induced cardiotoxicity [12] . The emergence of nanotechnology provides a powerful tool for effective delivery, responsive release, and reduction of toxicity of chemotherapeutic drugs [13,14] .…”
Section: Introductionmentioning
confidence: 99%
“…Still, chemotherapeutic drugs have problems such as poor stability, lack of tissue specificity, and short half-life, which not only lead to severe toxic side effects but also make chemotherapeutic drugs have a low concentration in tumor tissues, which can't achieve the therapeutic purpose [10,11] . In addition to this, it has also been shown that chemotherapy can lead to complications, such as anthracycline-induced cardiotoxicity [12] . The emergence of nanotechnology provides a powerful tool for effective delivery, responsive release, and reduction of toxicity of chemotherapeutic drugs [13,14] .…”
Section: Introductionmentioning
confidence: 99%